Data analysis of the U–Pb geochronology and Lu–Hf system in zircon and whole-rock Sr, Sm–Nd and Pb isotopic systems for the granitoids of Thailand - Romana E.C. Dew (2018)
© 2018 This data article provides zircon U–Pb and Lu–Hf isotopic information along with whole-rock Sm–Nd, Sr and Pb isotopic geochemistry from granitoids in Thailand. The U–Pb ages are described and the classification of crystallisation and inherited ages are explained. The petrography of the granitoid samples is detailed. The data presented in this article are interpreted and discussed in the research article entitled “Probing into Thailand's basement: New insights from U–Pb geochronology, Sr, Sm–Nd, Pb and Lu–Hf isotopic systems from granitoids” (Dew et al., 2018).